2016
DOI: 10.1158/1535-7163.mct-15-0758
|View full text |Cite
|
Sign up to set email alerts
|

Entrectinib, a Pan–TRK, ROS1, and ALK Inhibitor with Activity in Multiple Molecularly Defined Cancer Indications

Abstract: Activated ALK and ROS1 tyrosine kinases, resulting from chromosomal rearrangements, occur in a subset of non-small cell lung cancers (NSCLC) as well as other tumor types and their oncogenic relevance as actionable targets has been demonstrated by the efficacy of selective kinase inhibitors such as crizotinib, ceritinib, and alectinib. More recently, low-frequency rearrangements of TRK kinases have been described in NSCLC, colorectal carcinoma, glioblastoma, and Spitzoid melanoma. Entrectinib, whose discovery a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
201
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(211 citation statements)
references
References 43 publications
4
201
0
6
Order By: Relevance
“…Entrectinib is an oral inhibitor with low nanomolar potency against ALK, ROS1, and TRK kinases in enzymatic assays (85), and is able to effectively penetrate the blood-brain barrier (86). Its cellular IC 50 against ROS1 in Ba/F3 models is ~5 nM (86).…”
Section: Ros1-targeted Therapies In Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Entrectinib is an oral inhibitor with low nanomolar potency against ALK, ROS1, and TRK kinases in enzymatic assays (85), and is able to effectively penetrate the blood-brain barrier (86). Its cellular IC 50 against ROS1 in Ba/F3 models is ~5 nM (86).…”
Section: Ros1-targeted Therapies In Lung Cancermentioning
confidence: 99%
“…Its cellular IC 50 against ROS1 in Ba/F3 models is ~5 nM (86). Notably, entrectinib has failed to demonstrate preclinical activity against the ROS1 L2026M or G2032R resistance mutations (81), suggesting it likely has little role in treating crizotinib-resistant ROS1 -rearranged NSCLC.…”
Section: Ros1-targeted Therapies In Lung Cancermentioning
confidence: 99%
“…Given these findings, a primary breast cancer was suspected and she underwent a right central partial mastecto- pression of this ETV6-NTRK3 gene leads to formation of a chimeric tyrosine kinase that activates the Ras-MAPK and inositol-3'-kinase Akt pathways, which are noted to be the first event in the oncogenesis of SBC [11,12]. Furthermore, it was shown that a retroviral transfer of the same fusion gene induced SBC in mice [6].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with NTRK1 -rearranged NSCLC are particularly young and predominantly never-smokers. The pan-TRK inhibitors entrectinib and LOXO-101 are subject to clinical development and show promising activity in pre-clinical models and early clinical setting [68,99,102,103,104]. …”
Section: New Targets In Sclc and Nsclcmentioning
confidence: 99%